2008
DOI: 10.1108/17504970810867133
|View full text |Cite
|
Sign up to set email alerts
|

(Never) Mind the gap!

Abstract: Purpose -Focusing on gender as an aspect of diversity, the purpose of this paper is to review social studies research on technology, and suggest a new direction, with gender redefined from a gap to be eliminated to a difference to be explored. Design/methodology/approach -This paper is a literature review of research on gender, technology, and social studies from 1987 to 2007. Findings -Previously, men had more access and used more types of technology than women, but a shift to web-based computing eliminates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Gender should be seen as diversity to explore rather than a gap to eliminate. Gender equity focuses on treating different genders differently to remedy pre-existing condition of inequality (Crocco, Cramer, & Meier, 2008). CMC environments invite more diverse learners and educators should provide gender equity to support individuals, their needs and assist them to gain communication and collaboration skill sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender should be seen as diversity to explore rather than a gap to eliminate. Gender equity focuses on treating different genders differently to remedy pre-existing condition of inequality (Crocco, Cramer, & Meier, 2008). CMC environments invite more diverse learners and educators should provide gender equity to support individuals, their needs and assist them to gain communication and collaboration skill sets.…”
Section: Discussionmentioning
confidence: 99%
“…Although both genders may actively participate in CMC, it is inappropriate to assume that both genders possess an equal level of online social presence. Formerly, men had more access and used more types of technology than women, but a shift to web-based computing eliminates some gender gaps (Crocco, Cramer, & Meier, 2008). Women seem to be gaining territory in online communication.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in this study were Grade 11 boys who all attend a private day all-boys Canadian Association of Independent Association (CAIS) school located in Westmount, Quebec, Canada. Crocco, Cramer & Meier (2008) completed a study on gender, technology and social studies from 1987 to 2007. They showed that there was a limited number of studies on that topic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gender has always been a factor of disparity, and more so when use of IT is studied. The paper (Croco, Cramer and Meier 2008) urges decision makers to treat disparate groups differently so that pre-existing conditions of inequality of resources are remedied and gender equity attained. Unequal access, usage patterns and culture related differences have always plagued technology use and technology has always been viewed as a male domain.…”
Section: Gendermentioning
confidence: 99%